Increased Sensitivity of Glutathione S-Transferase P-Null Mice to Cyclophosphamide-Induced Urinary Bladder Toxicity - Conklin, Daniel J. (The American Society for Pharmacology and Experimental Therapeutics, 2009)
Hemorrhagic cystitis and diffuse inflammation of the bladder, common side effects of cyclophosphamide (CY) treatment, have been linked to the generation of acrolein derived from CY metabolism. Metabolic removal of acrolein involves multiple pathways, which include reduction, oxidation, and conjugation with glutathione. Herein, we tested the hypothesis that glutathione S-transferase P (GSTP), the GST isoform that displays high catalytic efficiency with acrolein, protects against CY-induced urotoxicity by detoxifying acrolein. Treatment of wild-type (WT) and mGstP1/P2 null (GSTP-null) mice with CY caused hemorrhagic cystitis, edema, albumin extravasation, and sloughing of bladder epithelium; however, CY-induced bladder ulcerations of the lamina propria were more numerous and more severe in GSTP-null mice. CY treatment also led to greater accumulation of myeloperoxidase-positive cells and specific protein-acrolein adducts in the bladder of GSTP-null than WT mice. There was no difference in hepatic microsomal production of acrolein from CY or urinary hydroxypropyl mercapturic acid output between WT and GSTP-null mice, but CY induced greater c-Jun NH(2)-terminal kinase (JNK) and c-Jun, but not extracellular signal-regulated kinase or p38, activation in GSTP-null than in WT mice. Pretreatment with mesna (2-mercaptoethane sulfonate sodium) abolished CY toxicity and JNK activation in GSTP-null mice. Taken together, these data support the view that GSTP prevents CY-induced bladder toxicity, in part by detoxifying acrolein. Because polymorphisms in human GSTP gene code for protein variants differing significantly in their catalytic efficiency toward acrolein, it is likely that GSTP polymorphisms influence CY urotoxicity. In addition, pretreatment with dietary or nutrient inducers of GSTP may be of use in minimizing bladder injury in patients undergoing CY therapy.